IMP/GTP balance modulates cytoophidium assembly and IMPDH activity - Keppeke, G; Chang, C; Peng, M; Chen, L; Lin, W; Pai, L; Andrade, L; Sung, L; Liu, J (BioMed Central, 2018)
Inosine monophosphate dehydrogenase (IMPDH), the rate-limiting enzyme in de novo GTP biosynthesis, plays an important role in cell metabolism and proliferation. It has been demonstrated that IMPDH can aggregate into a macrostructure, termed the cytoophidium, in mammalian cells under a variety of conditions. However, the regulation and function of the cytoophidium are still elusive.In this study, we report that spontaneous filamentation of IMPDH is correlated with rapid cell proliferation. Intracellular IMP accumulation promoted cytoophidium assembly, whereas elevated GTP level triggered disassociation of aggregates. By using IMPDH2 CBS domain mutant cell models, which are unable to form the cytoophidium, we have determined that the cytoophidium is of the utmost importance for maintaining the GTP pool and normal cell proliferation in the condition that higher IMPDH activity is required.Together, our results suggest a novel mechanism whereby cytoophidium assembly upregulates IMPDH activity and mediates guanine nucleotide homeostasis.